2017
DOI: 10.1039/c6ra28305e
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationships of Cu–ZrO2 catalysts for CO2 hydrogenation to methanol: interaction effects and reaction mechanism

Abstract: A systematic study on the Cu–ZrO2 catalysts with different oxygen vacancy concentrations and interaction gives a new approach for understanding the reaction mechanism of CO2 hydrogenation to methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 51 publications
(64 reference statements)
3
50
0
Order By: Relevance
“…Oxygen vacancies also influences magnetic 16 , photocatalytic 17 , optical 18 , wettability 19 , and electrical 20 , properties of the catalyst. In a recent study, it is discovered that the oxygen vacancies improves the overall conductivity and enhances the adsorption of reactants on its surface for organic conversions 21 . Additionally, oxygen deficient metal oxide greatly enhances the visible-light driven hydrogen production by trapping the photo-induced charges and preventing the electron-hole recombination 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen vacancies also influences magnetic 16 , photocatalytic 17 , optical 18 , wettability 19 , and electrical 20 , properties of the catalyst. In a recent study, it is discovered that the oxygen vacancies improves the overall conductivity and enhances the adsorption of reactants on its surface for organic conversions 21 . Additionally, oxygen deficient metal oxide greatly enhances the visible-light driven hydrogen production by trapping the photo-induced charges and preventing the electron-hole recombination 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The optimal rate constant and activation energy during HCOOH formation in the presence of Cu‐based heterogeneous catalyst are 2.57 × 10 −2 min −1 and 16.24 kJ mol −1 , respectively. Wang et al performed activity and selectivity measurements through CO 2 hydrogenation reaction for methanol production in a high‐pressure fixed‐bed flow stainless steel reactor. About 1.0 g of catalyst is first packed into stainless steel tubular reactor prior to its dilution with quartz sand.…”
Section: Reactor/process Designmentioning
confidence: 99%
“…For all the catalysts, the H 2 /Cu ratio is ca. 1.0 (1.02-1.00), which indicates full reduction of CuO to Cu 0 [39]. Figure 6a is the TPR profile of CuO, which shows a board reduction profile at 200-250 • C, with a main reduction peak α at around 233 • C. Sloczynski et al [40] and Velu et al [41] indicated α peak might be formed from the reduction of Cu + or crystallized copper oxide to metallic Cu.…”
Section: Reducibility Of Catalystmentioning
confidence: 99%
“…For all the catalysts, the H2/Cu ratio is ca. 1.0 (1.02-1.00), which indicates full reduction of CuO to Cu 0 [39]. Figure 6a is the TPR profile of CuO, which shows a board reduction profile at 200-250 °C, with a main reduction peak α at around 233 °C.…”
Section: Reducibility Of Catalystmentioning
confidence: 99%